"It was an unexpected bond": How an emerging participant-driven online social network may be enhancing an eLearning nutrition education & supplemental produce intervention. (May 2021) - Stotz, Sarah A; Lee, Jung Sun; Thompson, Jennifer Jo
Objective: The purpose of this paper is to describe a participant-driven, online text message-based social support network that emerged from an eLearning nutrition education and supplemental produce intervention. Methods: Adults (n = 20) who utilized a safety-net clinic for their healthcare participated in a 12-week smartphone-based nutrition education eLearning program using loaned smartphones. Participants also received a box of fresh produce weekly. Participants received weekly text message reminders to collect their produce, and from this researcher-initiated reminder text, a supportive, participant-led, all-group text message thread commenced. Researchers collected all 471 text messages in this all-group thread and included them in the qualitative content analysis of pre and post intervention focus groups. Results: The original design of the eLearning nutrition education program was to asynchronously engage learners with nutrition education resources. However, participants themselves initiated a robust group text message support system through which they shared encouragement, recipes, grocery shopping tips, and images of food they prepared with the produce box amongst themselves for the duration of the 12-week intervention. Conclusion: The novel nature by which these participants voluntarily engaged in this peer-to-peer nutrition education-focused text message conversation exemplifies participants becoming agents in their own learning experience and will be used to enhance future eLearning nutrition education experiences developed by our team.